Hukum Zakat Bagi Yang Berhutang Dalam Pandangan Muhammadiyah Dan Nahdlatul Ulama Kota Bandar Lampung - Masykuroh, Yufi Wiyos Rini; Lestari, Sri; Moelyono, Achmad (Universitas Islam Negeri Raden Intan Lampung, 2022)
One of the objectives of this research is to analyze, understand and find out the views of Muhammadiyah Regional Leaders and Nahdlatul Ulama Branch Managers in Bandar Lampung City regarding Zakat Law for those in Debt. The research method seen from this type of research is field research (field research). Data collection methods used in the form of books, journals, and interviews as well as documents and others. This study uses a qualitative method. Based on the results of the study, it was concluded that according to the Regional Leadership of Muhammadiyah, debt was a barrier for someone not to pay zakat. If someone has a debt then he should pay the debt first, if the debt has been paid and there is still remaining assets after paying the debt then he is obliged to pay zakat when it reaches the nisab, if it does not reach the nisab then it is not obligatory to pay zakat while according to the Nahdltul Branch Manager Scholars are of the opinion that if a person has a debt, he is obliged to pay zakat. Debt is not a barrier for someone not to pay zakat.Keywords: Bandar Lampung, Muhammadiyah, Nahdlatul Ulama, Payable Zakat